Colorado parenting time/visitation project: evaluation report (Center for Policy Research, 2007)
The Colorado Parenting Time Project was designed to assess whether identifying parents with visitation problems in the child support caseload and providing services aimed at resolving them improves parent-child contact and the subsequent payment of child support.